An Examination of the Effects of Unmet Psychological Needs on Mental and Physical Health - Beausoleil, Amélie (Université d'Ottawa / University of Ottawa, 2012)
The importance of psychological needs for optimal mental and physical well-being has been well documented within the literature. However, there remains little consensus on the definition of basic psychological needs, on which needs are most important or fundamental, and on how to best assess basic needs in individuals. The purpose of this dissertation was to develop and validate a comprehensive measure of fundamental psychological needs and to examine its predictive utility for both mental and physical health. To fulfil these objectives, measure construction and validation studies were conducted in 2 separate undergraduate student samples (N = 226; N = 283). Participants completed online self-report measures of emotional and psychological symptoms, negative life events, personality characteristics, and psychological needs. Factor Analyses of the Psychological Needs Questionnaire (PNQ) revealed that needs can be classified in a three-level multi-factorial confirmatory model and that self-worth and relationship types of psychological needs can be further divided into several, second-level factors. Results also indicated that the PNQ is reliable and possesses good construct validity as well as predictive utility for numerous psychological and physical problems. In addition, psychological needs moderated the relationship between depressive personality characteristics and mood. Future studies should examine the proposed needs-based model in a longitudinal fashion, both in community and clinical samples. In addition to functioning as a global introduction and providing an overview of the relevant literature, Chapter 1 proposes a new model of psychological needs. Chapter 2 describes in further detail the importance of each need identified by the new model, with a particular emphasis on the consequences associated with having each need unfulfilled. Chapter 3, 4, and 5 represent three academic journal articles resulting from the data collected in the current project. Finally, chapter 6 provides a global discussion of the entire dissertation.
Keywords: Psychological Needs; Mental health; Physical health; Need satisfaction